2006
DOI: 10.1016/j.jallcom.2005.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic reassessment of the Au–Te system

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. AbstractThe Au-Te binary system has been thermodynamically reassessed using the CALPHALD method. The excess Gibbs energy of the liquid phase was formulated with the Redlich-Kister expression and the AuTe 2 intermetallic phase was treated as a stoichiometric compound. A set of self-consistent thermodynamic parameters for each phase has been obtained. Good agreement is rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…(4) is dropped in Eq. (11). This is because the configurational entropy is already addressed in kMC simulations as the total number of possible events.…”
Section: Kinetic Monte Carlo Implementationmentioning
confidence: 99%
“…(4) is dropped in Eq. (11). This is because the configurational entropy is already addressed in kMC simulations as the total number of possible events.…”
Section: Kinetic Monte Carlo Implementationmentioning
confidence: 99%
“…Despite the wealth of data compiled by Afifi et al (1988), construction of phase diagrams to represent observed assemblages in many tellurium-bearing systems remains difficult due to the lack of reliable thermodynamic data for some minerals. New data for the system Ag-Au-X (X=S, Se, Te) (Echmaeva and Osadchii, 2008) is thus welcome, as are improved thermodynamic data for the systems Au-Te (Wang et al, 2006), Au-Bi-Sb (Wang et al, 2007) or the systems Au-Bi and Ag-Au-Bi (Servant et al, 2006;Zoro et al, 2007), the last four allowing greater accuracy in modelling the critical system Au-Bi-Te (Wagner, 2007;Tooth et al, 2008;see below). Fundamental thermodynamic information for Se-bearing systems has also become available (e.g., Xiong, 2003;Akinfiev and Tagirov, 2006a;Osadchii and Echmaeva, 2007), allowing detailed modelling of, for example, selenide-bearing vein and VHMS deposits (Layton-Matthews et al, 2008) and unconformity-related and sandstone-hosted uranium deposits.…”
Section: Phase Systems and Constraints On Mineral Stabilitiesmentioning
confidence: 99%
“…Note that we expect no Te accumulation, the maximum content being estimated to be as low as 0.15% 54 . 55 We turn now to the in situ TEM during the gold-seeded growth of ZnTe nanowires on two types of substrates, silicon and silicon carbide.…”
Section: Solid Nanoparticle Vs Liquid Nanodropletmentioning
confidence: 99%